Belimumab versus telitacicept in sequential treatment after rituximab for refractory lupus nephritis: a real-world multicentre study - Fei Han; Hong Pan; Yi Yang; Jianghua Chen; Jing Xue; Lan Lan; Yiting Chen; Pingping Ren; Yaomin Wang; Xin Lei; Jianhang Xu; Xiaochan Chen; et al. (Lupus Science and Medicine)
Objective Both belimumab and telitacicept are recognised blockers for B lymphocyte activation, both of which have been approved as add-on therapies for SLE in China. The aim of this study is to compare the efficacy of rituximab (RTX) followed by belimumab or telitacicept in a real-world cohort.Methods A total of 49 refractory lupus nephritis patients were enrolled from four independent centres, subsequently categorised into two treatment groups: belimumab group (n=35) and telitacicept group (n=14) based on their treatment following RTX. The outcomes of renal response rates were evaluated.Results In this study cohort, 63.3% presented with anti-dsDNA antibody positivity and 79.6% exhibited hypocomplementemia, with a mean Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K) Score of 13±6, estimated glomerular filtration rate (eGFR) of 76.2 (30.2, 113.7) mL/min and urinary protein creatinine ratio (uPCR) of 2.45 (0.77, 5.19) g/g. There was no significant differences between groups. After a follow-up duration of 26±12 months, renal objective remission rate was 80.0% (28 patients) in belimumab group and 85.7% (12 patients) in telitacicept group (difference, 5.7 percentage points, 95% CI, −25.8 to 26.8, p=1.000). Renal complete response was 54.3% (19 patients) in belimumab group and 78.6% (11 patients) in telitacicept group (difference, 24.3 percentage points, 95% CI, 9.7 to 47.8, p=0.194). The anti-dsDNA antibody, complement, eGFR, uPCR and SLEDAI-2K Score were improved in both groups with a significant reduction in prednisone dose. Major adverse effects included immunoglobulin deficiency, respiratory tract infection and urinary tract infection. No death occurred.Conclusions The sequential treatment of belimumab or telitacicept following RTX may represent a promising therapeutic approach in the management of refractory lupus nephritis. Further investigation is necessary to establish optimal protocols and long-term benefits.